IF SAME AS ANOTHER AND THERAPEUTIC COMMUNITY - Castillo Gaitán, Bernardo (2020)
The article aims to recognize the importance of incorporating philosophical texts in the theoretical foundation of programs for attention to people addicted to drugs. In the introduction he exposes the importance of the work Himself as Other in relation to the treatment of drug addicts; The theoretical foundations of the Therapeutic Community are presented as a model of care, a general summary of the work in question, continued with the relationship established between the mentioned work and the Therapeutic Community. It is concluded that Himself as Other, offers theoretical support for the development of programs for the care of people addicted to drugs.